Beyond Digital Skills: Addressing The Technical and Soft Skills Deficit in Malaysian TVET for the Manufacturing Sector - Zaid, Najmuddin Shah; Kamin, Yusri (Journal of Technical Education and Training, 2026)
This qualitative study confirms that the skills mismatch among Technical and Vocational Education and Training (TVET) graduates in Malaysia has shifted from traditional technical skills to digital skills especially in the manufacturing sector in Malaysia, in order to produce a high skilled worker that can support Malaysia’s policy aspirations under the New Industrial Master Plan (NIMP) 2030, to achieve the Gross Domestic Product (GDP) growth targets and creating high-value employment opportunities in the manufacturing sector. The primary aim of this study is to identify the digital skills required by TVET graduates to prepare them for the evolving demands of the workforce. Seven (7) industry experts from manufacturing sectors were selected through a snowball sampling method to address the three (3) research objectives. Data were analysed via Thematic analysis with the support of NVivo software for data management and interpretation. The findings indicate that the digital skills required of TVET graduates can be categorised into two (2) main dimensions: technical digital skills and digital soft skills. Both dimensions are pertinent in preparing graduates to adapt effectively to an increasingly digitalised industrial environment. Overall, the study supports Malaysia’s national policy initiatives to develop a digitally competent workforce capable of driving sustainable economic growth, within the manufacturing industry.